Commentary on Growth Strategy - Krueger, Anne O. (International Food Policy Research Institute, 1987)
Aboyade's chapter is a gold mine of hypotheses and lays the groundwork for considering interactions between economic policy and agricultural and nonagricultural growth extremely well. I find myself in agreement with most of his thrusts and hope to see further development of a number of his insights. It is difficult to comment on a chapter with which one is fundamentally in sympathy. In part, this is because commentators cannot reiterate those ideas with which they agree. In part, however, it is because there is so much that deserves attention and stimulates further thought.